Chapter 3 Managing the estate - McDonagh, Briony (Studies in Historical Geography, 2018)
Using material drawn from across eighteenth- and early nineteenth-century England, this chapter charts single, widowed and married women's contribution to estate management. It explores women's role in the financial management of landed estates as well as other more 'hands on' aspects of estate management, including setting and collecting rents, negotiating with tenants about rent, tenancies and repairs, supervising home farms, managing timber resources and otherwise determining estate policy